A study on the ordinances of three cities in Region 8 - Mangada, Ladylyn L. (1995)
This is a descriptive survey which attempted to document the ordinances of the Sangguniang Panlungsod of Tacloban, Ormoc and Calbayog from 1981 - 1992. The primary instrument that was used in the study was documentary analysis and four thousand two hundred seventy (4,270) ordinances constituted as variables. It was supplemented by an interview with thirty-six (36) local elected and twenty-five (25) appointed officials coming from separate terms, broadcast media practitioners, parish priests and NGOs and POs in the area. Findings indicated that 2) the three local legislatures enacted numerous appropriation ordinances, b) a minimum of one (1) bill can be passed into law per session, c) constituents' perceived ordinance enforcement as inadequate, and d) people were kept out from the decision-making organ since consultation/factfinding feedback were rarely employed as a legislative process prior to the Local Government Code of 1991.